Endoscopic sinus surgery and its effects on pulmonary function test in patients of chronic rhinosinusitis with nasal polyposis - Lyngdoh, Dameshwa S.; Behera, Subrat Kumar; Swain, Smruti; Pattnaik, Manoranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The human upper and lower respiratory tract share a close relationship in respect to existence of diseases. The objectives of this study were to evaluate the outcome of endoscopic sinus surgery with the Lund- Mackay staging system and to find any objective changes between the pre and post-operative pulmonary function test values in patients with chronic rhinosinusitis undergoing endoscopic sinus surgery. Methods: A total of 50 patients of CRSwNP refractory to maximal medical treatment (for 1 month) planned for endoscopic sinus surgery were included in the study. Results were assessed on the basis of pre and post-operative endoscopic and CT scores and PFT (FEV1, FVC and FEV1/FVC) values. Results: Postoperatively, Lund Mackay endoscopic and CT scores improved from the preoperative values, which were statistically significant with p values<0.05. Comparing FEV1/FVC, FVC and FEV1 values in three situations- preoperative versus postoperative 1 month, preoperative versus postoperative 3rd month and post-operative 1st month versus postoperative 3rd month, the difference between the means were found to be statistically significant (p=0.000), except for FVC between postoperative 3rd month and 1st month. Conclusions: This study provides objective evidence that patients with CRSwNP may have non clinical lower airway disease detected by PFT and ESS is effective in improvement of both nasal and lower airway disease as evident from the improvements in PFT values.